1999
DOI: 10.1110/ps.8.2.439
|View full text |Cite
|
Sign up to set email alerts
|

A novel clan of zinc metallopeptidases with possible intramembrane cleavage properties

Abstract: Abstract:Computer-based database searching and protein multiple sequence alignment has identified a novel clan of zinc metallopeptidases, which, by phylogenetic analysis, has been shown to contain six subfamilies. The family is characterized by four common transmembrane segments and three conserved sequence motifs. The combination of topology analysis and motif identification has detected three potential Zn 2ϩ coordinating residues. Only two of the sequences of this novel zinc metallopeptidase clan possess any… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(21 citation statements)
references
References 18 publications
(6 reference statements)
2
19
0
Order By: Relevance
“…SpoIVFB-S2P family members are intramembrane-acting, zinc metalloproteases and are found in a wide range of organisms, including many kinds of bacteria as well as flies and mammals (Lewis and Thomas 1999;Rudner et al 1999;Yu and Kroos 2000). In such systems, activation of the transcription factor is governed by two, successive proteolytic events known as Site-1 and Site-2 cleavage (Rawson et al 1997;Sakai et al 1998).…”
mentioning
confidence: 99%
“…SpoIVFB-S2P family members are intramembrane-acting, zinc metalloproteases and are found in a wide range of organisms, including many kinds of bacteria as well as flies and mammals (Lewis and Thomas 1999;Rudner et al 1999;Yu and Kroos 2000). In such systems, activation of the transcription factor is governed by two, successive proteolytic events known as Site-1 and Site-2 cleavage (Rawson et al 1997;Sakai et al 1998).…”
mentioning
confidence: 99%
“…Functions of the Ser-rich loop and the PDZ domain with its Cys-rich insert are unknown. The number of TMSs is uncertain but we favor the 8-TMS model proposed by Ha [19] in which TMSs 4, 5, and 6 form a conserved core predicted by sequence comparisons [2, 8]. A 3-TMS core was observed in the archaeal IMMP crystal structure [22].…”
Section: Membrane Topology and Extramembrane Domainsmentioning
confidence: 99%
“…Sequence analyses suggested that S2P is a polytopic membrane protein that is conserved in animals and archaea. Additional sequence comparisons identified similar proteins in the plant Arabidopsis thaliana and in diverse bacteria [2]. Shortly thereafter, mutational studies provided evidence that bacterial proteins SpoIVFB of Bacillus subtilis and YaeL (subsequently renamed RseP) of Escherichia coli are intramembrane metalloproteases (IMMPs) that cleave Pro-σ K and RseA, respectively [37].…”
Section: Introductionmentioning
confidence: 99%
“…It is known that a catalytic glutamic acid (E) and two metal-coordinating histidines (H) in the HEXXH motif and a third metal-coordinating aspartic acid (D) in the N(X) 7 DG motif together form a zinc-binding site, which is the catalytic center of the S2Ps (38). It is thought that the glutamic acid activates a water molecule for cleaving an extended and therefore accessible TMH substrate peptide bond (48).…”
Section: Five Putative S2psmentioning
confidence: 99%